Development of a Patient-Specific p.D85N-Potassium Voltage-Gated Channel Subfamily E Member 1–Induced Pluripotent Stem Cell–Derived Cardiomyocyte Model for Drug-Induced Long QT Syndrome. (June 2021) - Kim, Maengjo; Ye, Dan; John Kim, C.S.; Zhou, Wei; Tester, David J.; Giudicessi, John R.; Ackerman, Michael J.
Abstract : Background: Prior epidemiological studies demonstrated that the p.D85N-Potassium voltage-gated channel subfamily E member 1 (KCNE1) common variant reduces repolarization reserve and predisposes to drug-induced QT prolongation/torsades de pointes. We sought to develop a cellular model for drug-induced long QT syndrome using a patient-specific induced pluripotent stem cell-derived cardiomyocyte (iPSC-CM). Methods: p.D85N-KCNE1 iPSCs were generated from a 23-year-old female with an exaggerated heart rate-corrected QT interval response to metoclopramide (ΔQTc of 160 ms). Clustered regularly interspaced short palindromic repeats-associated 9 technology was used to generate gene-corrected isogenic iPSCs. Field potential duration and action potential duration (APD) were measured from iPSC-CMs. Results: At baseline, p.D85N-KCNE1 iPSC-CMs displayed significantly longer field potential duration (281±15 ms, n=13 versus 223±8.6 ms, n=14, P <0.01) and action potential duration at 90% repolarization (APD90; 579±22 ms, n=24 versus 465±33 ms, n=26, P <0.01) than isogenic-control iPSC-CMs. Dofetilide at a concentration of 2 nM increased significantly field potential duration (379±20 ms, n=13, P <0.01) and APD90 (666±11 ms, n=46, P <0.01) in p.D85N-KCNE1 iPSC-CMs but not in isogenic-control. The effect of dofetilide on APD90 (616±54 ms, n=7 versus 526±54 ms, n=10, P <0.05) was confirmed by Patch-clamp. Interestingly, treatment of p.D85N-KCNE1 iPSC-CMs with estrogen at a concentration of 1 nM exaggerated further dofetilide-induced APD90 prolongation (696±9 ms, n=81, P <0.01) and caused more early afterdepolarizations (11.7%) compared with isogenic control (APD90: 618±8 ms, n=115 and early afterdepolarizations: 2.6%, P <0.05). Conclusions: This iPSC-CM study provides further evidence that the p.D85N-KCNE1 common variant in combination with environmental factors such as QT prolonging drugs and female sex is proarrhythmic. Abstract : Supplemental Digital Content is available in the text.